DIGITALISASI PELAYANAN DESA MELALUI PROGRAM MANAHAYU E-DESA GIRIPURNO KOTA BATU - Ulfah, Irma Fitriana; Subekti, Tia; Haboddin, Muhtar (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2025)
This article explains the digitalization of village services in the Manahayu E-Desa Giripurno program. This began with the existence of different historical problems of village information, the central government, regional governments, or developed by the village itself. In addition, there are institutional problems and no infrastructure support for the digitalization of village services. This study uses the Jungwoo Lee government digitalization model using qualitative research methods. The results of the study show that: first, the actors who play an important role in the management of the Manahayu E-Desa program are the village head and village secretary whose service implementation is carried out by the Head of Government, Head of Service, Head of General Affairs and their staff. Second, this program can be accessed via http://e-desa.desagiripurno.id. Data integration in this program is shown by the existence of population data archives, so making letters is sufficient by entering the resident's NIK. In addition, the registration number automatically appears and the signature of the village head using a QR barcode. Third, it was recorded that as of December 6, 2024, Giripurno Village had issued 3,345 letters. Fourth, in terms of management, the Manahayu E-Desa program has been running well, strengthened by the existence of Village Regulations and funding support from the Village Budget. Although this program has not been integrated with the Community online, it has been able to facilitate and accelerate services in Giripurno Village